Cross-border insolvency law international instruments and commentary - Wessels, B. (Bob), 1949- (Kluwer Law International, 2015)
"Recent insolvency cases highlight the growing importance of cross-border insolvency matters in international transactions. In order to obtain relevant information essential for conduct in such transactions, an insolvency lawyer needs to have access to the many relevant instruments that have been introduced and implemented in recent years, but that until now have not been available in any single place.00This very useful volume collects, for the second time in one source, all important international and regional legal instruments relating to insolvency of companies and consumers, as well as to corporate rescue law. The book includes international and regional conventions, model laws, EU regulations and directives, uniform rules and guiding principles produced by various international bodies (such as the World Bank, the United Nations Committee on International Trade Law, the American Law Institute, and INSOL International), and international and European restatements of insolvency law by scholars."--Wolters Kluwer CCH Website.